A SEIR model for control of infectious diseases with constraints - M. H. A. Biswas; L. T. Paiva; MdR de Pinho (Mathematical Biosciences and Engineering)
Optimal control can be of help to test and compare different vaccination strategies of a certain disease.In this paper we propose the introduction ofconstraints involving state variables on an optimal control problem applied to a compartmental SEIR (Susceptible. Exposed, Infectious and Recovered) model. We study the solution of such problems when mixed state control constraints are used to impose upper bounds on the available vaccines at each instant of time. We also explore the possibility of imposing upper bounds on the number of susceptible individuals with and without limitations on the number of vaccines available. In the case of mere mixed constraints a numerical and analytical study is conducted while in the other two situations only numerical results are presented.